Pandangan Pentadbir terhadap Implementasi Proses Perubahan Terancang pada Sekolah Bestari di Malaysia - Hamzah, Mohd Izham bin Mohd; Azman, Norzaini (SOSIOHUMANIKA, 2009)
ABSTRACT: The process of planned change is a systematic effort to realign and redevelop educational organization in order to respond to felt needs and adapt to changing educational environments. A dynamic planned change involves determining what requires changes and when and how the changes should take place and be managed. The Ministry of Education in Malaysia has systematically planned the establishment of Smart Schools to ensure that the goals of its establishment and the implementation process are successful. Thus, the purpose of this study is to examine and describe the Smart Schoolsâ administratorsâ perceptions on the process of planned change introduced in the Smart School system. The qualitative study uses multiple case study involving five Smart Schools. Data was gathered through semi-structured interviews. The sample consisted of school principals, assistant school principals, IT coordinators and subject heads. Results show that some of the administrators have positive perceptions and that they fully support the process of planned change in their schools. The administrators also faced problems when the planned change was introduced simultaneously within the same period of time. In each case, they could not decide which change should be given priority. The study suggests that the process of planned change can be implemented successfully with a well structured co-ordination within the components of the plan.Key words: planned change, Smart School, administrators and positive perceptions.Â Â Â About the Authors: Dr. Mohd Izham bin Mohd Hamzah ialah Pensyarah di Fakulti Pendidikan UKM (Universiti Kebangsaan Malaysia). Beliau mendapat Ijazah Sarjanamuda Sains (dengan Kepujian) Botani dari UKM (1986); Ijazah Sarjana Pendidikan Pengurusan & Pentadbiran (1997); dan Ijazah Doktor Falsafah (Ph.D.) dari UM (Universiti Malaya) dalam bidang Pentadbiran Pendidikan (2006). Beliau pernah menjadi Penyelaras Program Khas Pensiswazahan Guru Besar dan sekarang menjawat jawatan Ketua Pengurusan Kualiti, Fakulti Pendidikan UKM Bangi, Selangor Darul Ehsan, Malaysia. Dr. Norzaini Azman ialah Pensyarah di Fakulti Pendidikan UKM. Bidang penyelidikan utama beliau ialah sistem dan governan, perbandingan dan pengantarbangsaan Pendidikan Tinggi serta psikologi pendidikan dewasa. Beliau telah menerbitkan lebih dari 50 kertas kerja pada peringkat kebangsaan dan antarabangsa dalam bidang pendidikan tinggi dan dewasa dan psikologi pendidikan. Beliau adalah Felo Penyelidik Bersekutu di Institut Penyelidikan Pendidikan Tinggi Negara (IPPTN) dan ahli kepada Standing Conference on Teaching and Research in Higher Education (SCUTREA) dan Higher Education Research and Development (HERDSA). Alamat e-mail beliau adalah: norzai12@yahoo.comHow to cite this article? Hamzah, Mohd Izham bin Mohd & Norzaini Azman. (2009). âPandangan Pentadbir terhadap Implementasi Proses Perubahan Terancang pada Sekolah Bestari di Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.1 [Mei], pp.75-88. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (March 5, 2009); Revised (April 7, 2009); and Published (May 20, 2009).